Sports Specialization in Young Male Kayakers: Studying the young athlete, sports selection process, performance and equipment set-up - Fernandes, Rui António de Almeida Duarte (2024)
Tese de Doutoramento em Ciências do Desporto apresentada à Faculdade de Ciências do Desporto e Educação Física